A Case Report of Suicide Attempt Caused by Acute and Transient Psychotic Disorder during the COVID-19 Outbreak - Kai Zhang; Yudong Shi; Huanzhong Liu; Kenji Hashimoto (Case Reports in Psychiatry)
We reported a case of suicide attempt caused by acute and transient psychotic disorder during the COVID-19 outbreak, which broke out in December 2019 in Wuhan. An epidemic of infectious diseases brought great psychological pressure to the public. During this period, a 20-year-old man went to the hospital repeatedly because he suspected that he was infected, with suspicious auditory hallucinations, self-laughter, primary delusions, victimization delusions, relationship delusions, and suicide attempts. He was diagnosed with Acute Transient Psychotic Disorder. 0.1 g bid Quetiapine was given orally, then gradually increased to 0.4 g per day, supplemented by cognitive therapy. The patient was discharged from hospital in relief of symptoms on February 9th. Conclusion. During the epidemic period, in addition to strengthening the protection work, we should also monitor the mental and psychological state of the population to prevent mental illness caused by coronavirus.